Affordable Housing Development : Financial Feasibility, Tax Increment Financing and Tax Credits /: Financial Feasibility, Tax Increment Financing and Tax Credits. ([2019]) - Luque, Jaime, 1981-; Ikromov, Nuriddin; Noseworthy, William B
No abstract available